Improving crude oil storage tank heating and blending using multiple hot jet sprays: An experimental and numerical study - M. Shahnazari Sani; D.D. Ganji; A. Ramiar; Kh Hoseinzadeh (Case Studies in Thermal Engineering)
A significant factor in the storage and blending of crude oil in reservoirs and its transfer and transmission to the pipeline in cold regions is sufficient heating and blending in the reservoir to reach the desired temperature and quality. Rapid heating and better blending prevent it from becoming sludg and jelly-like in the pipeline and damaging facilities, pumps, etc. The foreign ship, at the right operational time, sends its cargo to the tank or receives it from it and prevents the company from receiving damages due to the ship's time waste. In crude oil storage tanks, considering that crude oil has a low thermal conductivity coefficient, heat transfer in the inner layers of crude oil takes place slowly, so multiple hot crude oil flow nozzles are used to inject into the reservoir to rate up heating and better blending. The blending and homogenization or blending of stored crude oil in storage tanks, its heating takes place at three molecular, vortex, convection, which as a result, the rate of each of them increases, the rate of blending and homogenization and also heating increases. The process of heat transfer and blending is essentially dependent on the buoyancy of the fluid resulting from the hot crude oil jet flow by the nozzles. The Froude number along with the Reynolds number and diffusion number stronger indicates better buoyancy and stronger and faster heat transfer and more homogeneous blending and vice versa. Increasing or decreasing the temperature and output velocity of hot crude oil from the nozzles, changing the arrangement of the nozzles and their number, changing the diameter and angle of the nozzle throw can have a significant effect on increasing or decreasing the Froude and Reynolds numbers and diffusion number and as a result, increase or decrease the rate of heating and blending of stored crude oil inside the tank, which is examined in this activity experimentally and numerically. The finite volume method and standard k − ε turbulence model are used to numerically investigate the heat transfer features of crude oil inside the floating roof tank under the hot crude oil jet flow heating mode. By choosing the correct arrangement of hot jet flow nozzles, the appropriate diameter of the nozzles, the temperature and output velocity of the hot jet flow fluid, the appropriate flow rate of the jet, the appropriate throw angle of the hot jet flow nozzles, etc., the heating and blending rate of the crude oil storage tank can be increased by 50–70 percent compared to when submerged heat exchanger are used inside the tank, which is currently common, and reduce its operational heating and blending time by the same amount.